2021
DOI: 10.3389/fonc.2021.635731
|View full text |Cite
|
Sign up to set email alerts
|

The Progress in the Treatment of Hepatocellular Carcinoma With Portal Vein Tumor Thrombus

Abstract: Hepatocellular carcinoma (HCC) is one of most prevalent cancer and is a serious healthcare issue worldwide. Portal vein tumor thrombus (PVTT) is a frequent complication and remains as the blockage in the treatment of HCC with high recurrence rate and poor prognosis. There is still no global consensus or standard guideline on the management of HCC with PVTT. In western countries, Sorafenib and Lenvatinib are recommended as the first-line treatment options for HCC patients with PVTT where this condition is now r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 139 publications
(199 reference statements)
0
23
0
Order By: Relevance
“…Macroscopic tumor thrombosis in HCC is one of the most serious conditions associated with poor prognosis, representing the Barcelona Clinic Liver Cancer stage C ( 5 ). This condition is generally considered an indication for systemic agents rather than local therapies because of its association with rapid intrahepatic and extrahepatic metastases, as well as concerns about maintaining liver function ( 21 ). In certain patients with this condition, favorable long-term outcomes through surgical resection, including tumor thrombus, have been reported ( 10 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic tumor thrombosis in HCC is one of the most serious conditions associated with poor prognosis, representing the Barcelona Clinic Liver Cancer stage C ( 5 ). This condition is generally considered an indication for systemic agents rather than local therapies because of its association with rapid intrahepatic and extrahepatic metastases, as well as concerns about maintaining liver function ( 21 ). In certain patients with this condition, favorable long-term outcomes through surgical resection, including tumor thrombus, have been reported ( 10 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…For now, molecularly targeted drugs are still the main treatment strategy for advanced HCC (72)(73)(74). Among them, Sorafenib is the most widely used (75)(76)(77). In order to overcome the shortcomings of Sorafenib, newly molecular targeted drugs including Regorafenib, Lenvatinib and Cabozantinib have been approved for marketing one after another (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefit was not significant in patients whose PVTT affected the main trunk or contralateral branch (Vp4). A similar study in a Chinese population reported that as long as the PVTT was confined to the first-order branch of the portal vein, the patient may be eligible for resection (41). Resection most commonly precedes hepatic dissection.…”
Section: Portal Vein Tumor Thrombusmentioning
confidence: 91%